Post Covid-19 Syndrome: case study (Research, Society and Development, 2022)
Post-Covid-19 Syndrome (PCS) or long Covid (CL) is a clinical condition arising from the SARS-CoV-2 infection that some people experience after the end of Covid-19, with a variety of symptoms such as fatigue, chronic pain, shortness of breath, cognitive dysfunction, loss of smell, dizziness, headaches and anxiety disorder and post-traumatic stress, impacting quality of life. Patients with inflammatory and autoimmune diseases such as Fibromyalgia (FM) represent a particularly vulnerable group to the development of LC due changes in the Autonomic Nervous System (ANS), use of glucocorticoids and the isolation and sedentary lifestyle imposed by the pandemic intensify chronic pain, emotional and sleep changes. The aim of this study was to report a case of PCS in a patient with FM to which a treatment protocol consisting of acupuncture and myofascial release at the outpatient clinic of a public hospital in Teresina-PI. Data were collected using Depression Anxiety Stress (DASS-21), Mini Mental State Examination (MMSE), Nordic Musculoskeletal Symptom Questionnaire (NSO), Quality of Life Assessment Questionnaire (WHOQOL-BREF), Quality Index Sleep Test (PSQI), Visual Analog Scale (VAS) and Algometry. The results showed a reduction in stress, anxiety and depression levels, a decrease in muscle pain, an increase in PPT with a reduction in withdrawal from routine activities, impacting on the improvement of the general quality of life and sleep. It is concluded that acupuncture treatment associated with myofascial release is an effective alternative for improving PCS in patients with FM.